Power Relations in Waste Management Policy in Jakarta Provincial Government: Case Study of Waste Bank Management Policy in North Rawa Badak Urban Village - Safira, Bianca Ananda; Angela, Deni (Borong Newinera Publisher, 2024)
This study aims to examine the implementation of waste management policies through waste banks in North Rawa Badak Urban Village, using Merilee S. Grindle's Policy Implementation theory as a framework. Additionally, it aims to identify the key actors and power relations involved in the policy's execution and to outline the factors affecting policy implementation, utilizing the model proposed by Ripley and Franklin. This study employs a qualitative research method, gathering data through literature review, interviews, and observation. The subjects of this study included North Jakarta Environmental Agency, the North Rawa Badak Urban Village Waste Bank, environmental expert and academic, and Karang Taruna North Rawa Badak Urban Village. The study's findings indicate that the implementation of waste management policies through waste banks in North Rawa Badak Urban Village has not aligned with the expected standards of smooth functioning, level of compliance, performance, operational effectiveness, and expected impact. Consequently, the waste bank has not achieved optimal results and has not been successful in its implementation.